Translation, cross-cultural adaptation and validation of SinoNasal Outcome Test (SNOT): 22 to Brazilian Portuguese - Kosugi, Eduardo Macoto [UNIFESP] (2011)
Quality of life questionnaires have been increasingly used in clinical trials to help establish the impact of medical intervention or to assess the outcome of health care services. Among disease-specific outcome measures, SNOT-22 was considered the most suitable tool for assessing chronic rhinosinusitis and patients with nasal polyps. AIMS: To perform translation, cross-cultural adaptation and validation of the SNOT-22 to Brazilian Portuguese. METHODS: Prospective study involving eighty-nine patients with chronic rhinosinusitis or nasal polyps submitted to functional endoscopic sinus surgery, who answered the questionnaire before and after surgery. Furthermore, 113 volunteers without sinonasal disease also answered the questionnaire. Internal consistency, test-retest reliability, measure validity, responsiveness and clinical interpretability were assessed. RESULTS: Mean preoperative, postoperative and no sinonasal disease scores were 62.39, 23.09 and 11.42, respectively (p<0.0001); showing validity and responsiveness. Internal consistency was high (Cronbach's alpha = 0.9276). Reliability was sufficiently good, considering inter-interviewers (r=0.81) and intra-interviewers within a 10 to 14 day-interval (r=0.72). Surgery effect size was 1.55. Minimally important difference was 14 points; and scores up to 10 points were considered normal. CONCLUSION: The Brazilian Portuguese SNOT-22 version is a valid instrument to assess patients with chronic rhinosinusitis and nasal polyps.